Strategic Communication – Contemporary Perspectives - Sharam Alghasi; Ester Conings Vanvik; Jens Barland; Jesper Falkheimer (Cappelen Damm Akademisk/NOASP, 2024)
Strategic communication is emerging as a widespread professional field. When communication is strategic, the aim is purposeful impact. In society, politics, civil society and markets, new techniques and practices are being developed for communication to achieve such impact. Strategic Communication – Contemporary Perspectives explores those changes. In sum, these 10 chapters offer a range of perspectives illustrating contemporary trends in the field of strategic communication. Researchers at the Department of Communication at Kristiania University College, along with external co-authors, have written this scientific anthology aimed at research colleagues and others interested in keeping current on trends in strategic communication.
Keywords: 650; societal aspects of communcations; market logic; business logic; organization; leadership; strategic communications